Plan de negocios para la creación de un proveedor de alimentos para restaurantes en la ciudad de Quito - Muñoz Alarcón, Daniela Cristina (2013)
This project deals with the feasibility of establishing a supplier of meats and seafood, specializing in upscale restaurants. It conducted research for industry wholesale of food, beverages and snuff. The analysis found that the GDP of Ecuador has had a significant increase of 8% between 2011 and 2012 according to data obtained from the National Information System, and the industry in which we find ourselves, is one of the largest contribution to 15.05%. Also analyzed that there is a growing consumption of meat 2%, between 2012 and 2013, according to data collected by FAO, which is one of the main products to be marketed. Our target market are the restaurants, so we studied the Gastronomic market growth, which has become investigated about 8%, which represents a very attractive figure to carry out a project of this nature as it is the third fastest growing industry according to the ministry of Industry and Competitiveness. The design of market research was conducted through qualitative research through interviews with experts and in-depth interviews with owners and managers of luxury restaurants, to obtain primary data. In the investigation, it was extremely valuable to gather information regarding their historic inventories, who are your current suppliers, each time they buy products and what are the foods that harm them. The Marketing strategy to be applied for this project is based on the creation of a storage facility and adding value, specializing in steaks and seafood for distribution in major luxury restaurants north of the capital. It will offer as a differentiator home delivery in refrigerated trucks, with excellent quality products vacuum packaging. We will analyze the marketing mix, with special attention to the promotion to be done to achieve satisfied customers become loyal to our company. This business is aimed; meet a latent need in catering Quito, within the scope of upscale restaurants, as many providers who use the restaurants are individuals who do not offer the best quality products. That's why this center will select the best product, clean and deliver to our customers, saving them time to their employees. To start this project required an investment of $ 320.959,94, which will be financed by 80% by the shareholders, and the balance on credit. For sales projection, took into consideration the historical inventories supplied by the same restaurants, this projection was set at $ 1,536.392,63 annually. In detailing the profitability of this project was conducted in cash flows three scenarios (pessimistic, average and optimistic), for which we had a discount rate calculated by the method CAMP, the TIR are establishing 33,27% in deleveraged and 24,69% in the leveraged while the VAN was at 175.433,61 deleveraged and -139.930,07 in leveraged. The point of equilibrium is established at $ 258.366 per year is $ 21.530,05 per month, a figure that can cover fixed costs. Also, note that the initial investment is recovered in the first year of operation itself projected sales are met and there is no kind of unexpectedly. It was also analyzed the business proposal to the investor, and will detail the profits it when placing their capital in my company. Flow is estimated the investor, which takes into account a discount rate of 16.49% WACC calculated by the method, which resulted in us an IRR of 24% and a NPV of $ 104.743,06. Finally, there are the project's findings and recommendations can be given once it has started this project.